"Can't use old keys to open new doors": relational desistance mechanisms within community violence interventions - Simonsson, Peter (Inquiry, 2025)
Community Violence Intervention (CVI) programs show promising results in reducing health disparities such as firearminjury and violence. However, the process by which these programs bring about positive change is less well due to programvariations and the focus of existing studies. Hence, program components and strategies used in day-to-day community violenceintervention work are less clear. To address this gap, this study used in-depth interview data focused on understanding theearly engagement of participants in an east coast United States community violence intervention program (n = 32). Questionsfocused on the process by which credible messengers as outreach workers motivate at-risk individuals to join the program,obtaining descriptions of the personal mentoring and cognitive change efforts driving desistance. Three key themes emerged:outreach workers use their own “lived experience” or self-narratives to build trust and motivate at-risk individuals to joinand stick with programing; outreach workers and participants form a unique relationship through which participants arebuoyed by belonging to a new “family”; and participants acquire new skills and prosocial peer networks that help themnavigate away from the streets. Together, these processes support at-risk individuals through what might be best understoodas a social movement as opposed to an individualistic process of “corrections” or reform.